A Hybrid Approach to User Interface Design: Integrating DT and QFD with Usability Evaluation in a Detection-Based Classification System for the Sugarcane Industry - Caesaron, Dino; Adyatama, Achmad Reza; Mufidah, Ilma; Fitriani, Elsa; Daliana, Nadia; Utama, Nur Ichsan (Engineering, Technology & Applied Science Research, 2025)
Quality User Interface (UI) and User Experience (UX) design are crucial for web system success, as poor design can hinder information retrieval and cause miscommunication. To address this challenge within a specific industrial setting, this study presents a detailed case study on the design and development of an intranet web system for a sugarcane processing company. A combined methodology of Design Thinking (DT) and Quality Function Deployment (QFD) was applied to capture user needs and translate them into a functional, user-centered UI/UX design. The design process involved iterative prototyping and continuous user feedback. Evaluation of the prototype using the System Usability Scale (SUS) resulted in a score of 85, classified as "excellent". These findings demonstrate that integrating DT and QFD substantially enhances UI/UX design effectiveness. The findings from this case study offer practical blueprints and valuable insights for practitioners aiming to implement similar user-centered design projects, particularly within the agroindustry sector or other comparable contexts.